Corrigendum: Freshwater savings from marine protein consumption (2014 Environ. Res. Lett. 9 014005) - Jessica A Gephart; Michael L Pace; Paolo D’ Odorico (Environmental Research Letters, 2014)
The full text of this article is available in the PDF provided.